WIN18,446 enhances spermatogonial stem cell homing and fertility after germ cell transplantation by increasing blood-testis barrier permeability - Hiroko MORIMOTO; Mito KANATSU-SHINOHARA; Takashi SHINOHARA (The Society for Reproduction and Development, 2023)
Spermatogonial stem cells (SSCs) possess a unique ability to recolonize the seminiferous tubules. Upon microinjection into the adluminal compartment of the seminiferous tubules, SSCs transmigrate through the blood-testis barrier (BTB) to the basal compartment of the tubule and reinitiate spermatogenesis. It was recently discovered that inhibiting retinoic acid signaling with WIN18,446 enhances SSC colonization by transiently suppressing spermatogonia differentiation, thereby promoting fertility restoration. In this study, we report that WIN18,446 increases SSC colonization by disrupting the BTB. WIN18,446 altered the expression patterns of tight junction proteins (TJPs) and disrupted the BTB in busulfan-treated mice. WIN18,446 upregulated the expression of FGF2, one of the self-renewal factors for SSCs. While WIN18,446 enhanced SSC colonization in busulfan-treated wild-type mice, it did not increase colonization levels in busulfan-treated Cldn11-deficient mice, which lack the BTB, indicating that the enhancement of SSC colonization in wild-type testes depended on the loss of the BTB. Serial transplantation analysis revealed impaired self-renewal caused by WIN18,446, indicating that WIN18,446-mediated inhibition of retinoic acid signaling impaired SSC self-renewal. Strikingly, WIN18,446 administration resulted in the death of 45% of busulfan-treated recipient mice. These findings suggest that TJP modulation is the primary mechanism behind enhanced SSC homing by WIN18,446 and raise concerns regarding the use of WIN18,446 for human SSC transplantation.